Reversal of corticosteroid insensitivity by p38 MAPK inhibition in peripheral blood mononuclear cells from COPD - Khorasani,N; Baker,J; Johnson,M; Chung,KF; Bhavsar,PK (International Journal of Chronic Obstructive Pulmonary Disease, 2015)
Background: Corticosteroids (CS) have limited efficacy in the treatment of chronic obstructivepulmonary disease (COPD). p38 mitogen-activated protein kinase (MAPK) activation isincreased in lung macrophages of COPD. We investigated whether p38 MAPK inhibitioncan modulate CS insensitivity of peripheral blood mononuclear cells (PBMCs) from patientswith COPD.Methods: PBMCs from patients with COPD (n=8) or healthy smokers (n=8) were exposed tolipopolysaccharide (LPS) with a selective p38 MAPK inhibitor (GW856553; 10-10–10-6 M),with dexamethasone (10-10–10-6 M), or with both. Phosphorylated glucocorticoid receptor (GR)was measured by Western blot.Results: Baseline (P,0.01) and LPS-induced (P,0.05) CXCL8 release was greater in PBMCsfrom COPD compared to healthy smokers. Inhibition of LPS-induced CXCL8 release by dexamethasone(10-6 M) was reduced, and baseline and LPS-induced p38 MAPK activation increasedin PBMCs of COPD. GW856553 (10-9 and 10-10 M) synergistically increased the inhibitoryeffect of dexamethasone (10-8 and 10-6 M) on LPS-induced CXCL8 release in COPD. Similarresults were obtained for IL-6 release. GW856553 inhibited dexamethasone- and LPS-activatedphosphorylation of serine 211 on GR. CS insensitivity in COPD PBMCs is reversed by inhibitionof p38 MAPK activity, partly by preventing phosphorylation of GR at serine 211.Conclusion: p38 MAPK inhibition may be beneficial in COPD by restoring CS sensitivity.